Penerapan Teknik Pembelajaran Ekspositori: Strategi Efektif Meningkatkan Pemahaman Belajar Siswa - Tiara Asnanda; Intan Lestari; Gusmaneli Gusmaneli (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This article aims to describe (tell) the Basic Concepts of Expository Learning Strategies which can improve students' understanding in learning. This research uses library research methodology and is qualitative in nature, because the data collected uses textual analysis contained in books and journals related to expository learning strategies. The results of this research are the first in this study to obtain a basic understanding of expository learning strategies. These two principles. The three weaknesses and advantages. The four steps. The five applications of this strategy are to increase students' understanding during the learning process.